Pengaruh E-WOM, Live Streaming Dan Viral Marketing Terhadap Keputusan Pembelian Produk Somethinc Di TikTok - Prameswari, Levi Andini Cantika; Djaelani, Abdul Kodir; Millaningtyas, Restu (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to analyze the effect of E-WOM, live streaming, and viral marketing on somethinc purchasing decisions on tiktok. This type of research is using quantitative methods. The population is students of Islamic university campuses in Malang City, namely Unisma, UMM, UIN with a sample size of 140 respondents and the use of sampling techniques, namely non-probability sampling. The data source comes from primary data through distributing questionnaires and using SPSS version 25.0 as a data analysis tool. The test results show simultaneously  and partially that E-WOM (X1), Live Streaming (X2), and Viral Marketing (X3) have a positive effect on Purchasing Decisions (Y). Keywords :       E-WOM, Live Streaming, Viral Marketing, Purchase Decision.